2021
DOI: 10.3390/nu13124465
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D and Dental Caries in a Sample of Canadian and American Preschool-Aged Children

Abstract: Background: Inadequate vitamin D levels may increase the risk of caries during childhood. The purpose of this study was to investigate the association between 25-hydroxyvitamin D (25(OH)D) status and severe early childhood caries (S-ECC) in preschool children. Methods: Data were obtained from children <72 months of age in two case–control studies in Winnipeg, Manitoba and Richmond, Virginia. Serum analysis assessed 25(OH)D, calcium and parathyroid concentrations. Data on demographics, dental history and ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…38 Additionally, a recent case-control study with a sizable sample size discovered a link between lower caries risk and greater 25-(OH)D concentrations. 39 The findings of this study indicate inadequate vitamin D concentrations are related to an increased risk of childhood caries and have a lot of supporting evidence. [40][41][42] In a study of schoolchildren in Taiwan, calcium intake was only related to dental health in a crude model.…”
Section: Discussionmentioning
confidence: 67%
“…38 Additionally, a recent case-control study with a sizable sample size discovered a link between lower caries risk and greater 25-(OH)D concentrations. 39 The findings of this study indicate inadequate vitamin D concentrations are related to an increased risk of childhood caries and have a lot of supporting evidence. [40][41][42] In a study of schoolchildren in Taiwan, calcium intake was only related to dental health in a crude model.…”
Section: Discussionmentioning
confidence: 67%
“…The study by Mellanby and Pattison, published in 1928, provides the first evidence that vitamin D deficiency is associated with dental caries in children [7,8]. A growing body of studies and evidence shows that low serum concentrations of 25-hydroxyvitamin D (25(OH)D) are associated with increased caries experience [2,[8][9][10][11]. It has even been reported that low 25(OH)D levels in the mother during pregnancy increase the risk of ECC in children [9,10,12].…”
Section: Vitamin D Deficiency In Pediatric Dentistrymentioning
confidence: 99%
“…A growing body of studies and evidence shows that low serum concentrations of 25-hydroxyvitamin D (25(OH)D) are associated with increased caries experience [2,[8][9][10][11]. It has even been reported that low 25(OH)D levels in the mother during pregnancy increase the risk of ECC in children [9,10,12].…”
Section: Vitamin D Deficiency In Pediatric Dentistrymentioning
confidence: 99%
“…19 There is evidence of an association between the nutritional status, specifically vitamin D and calcium levels, and severe early childhood caries (S-ECC) in preschool children. 20 Still, in severe vitamin D deficiency, there is a high risk of non-syndromic amelogenesis imperfecta and dentinogenesis imperfecta, enamel hypoplasia, hypomineralization/maturation defects, and the abnormal shapes of permanent teeth. 21 When present, developmental enamel defects are also frequently associated with dental caries in preschool children, 22 and clinically occur with discoloration and esthetics problems, tooth sensitivity, wear, and erosion.…”
Section: Introductionmentioning
confidence: 99%